The civil organizations of the Korean diaspora and its implications for the public diplomacy of South Korea: a comparative study of Argentina and Mexico - Chaure, Desireé Nair (2020)
The present paper tries to analyze the actions of civil organizations of the Korean diasporas in Argentina, a non APEC country, and Mexico, an APEC country, in order to determine its potential to constitute an effective diaspora diplomacy and their influence in the conformation of South Korea's soft power. It will also examine the possibilities to increase cooperation between diaspora organizations and the South Korean Government, with the aim to promote and improve its public diplomacy. To understand the role of diaspora civil organization in the development of South Korean diplomacy, first we must consider the history of South Korea's relations with both nations and the characteristics of immigration in each country. In addition for the theoretical frame we will take the conceptualization of soft power and public diplomacy.